When The East Shall Greet The West By The Way Of The Panama - Genevieve Scott::::::::: (H. Kurkus Dugdale Co. Music Publishers and Dealers)
5 p. Dedicated to San Francisco. H. Kirkus Dugdale Co., c1914. Fred Miller was a resident of Fresno. CSU Fresno copy is a photocopy.